Surrogacy Law: Iran’s Framework and Structural Constraints in Indonesia - Azzahra, Khalida; Ibtiani, Heni; Amelia, Putri (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN EKONOMI DAN HUKUM ISLAM), 2025)
Surrogacy has been legalized in Iran, the only Muslim-majority country to formally accommodate the practice within its healthcare and legal systems. In contrast, despite a high prevalence of infertility, the Indonesian legal order remains closed to surrogacy due to persistent juridical, ethical, and theological contestation. Existing scholarship has largely examined these jurisdictions in isolation or has focused predominantly on theological prohibition, leaving limited comparative analysis of the structural limits of legal transplantation. Addressing this gap, this study employs a normative-comparative legal method to analyze primary legal materials, including Iran’s Civil Code and Indonesian health and family laws. The findings demonstrate that Iran validates surrogacy through Article 10 of its Civil Code and flexible Jaʿfari jurisprudence. Conversely, the study shows that surrogacy in Indonesia is structurally precluded by three interlocking dimensions: civil-contractual incompatibility with the requirement of a lawful cause, restrictive medical-administrative regulations grounded in mater semper certa est, and a dominant Sunni legal consensus classifying surrogacy as zina, thereby threatening the preservation of lineage (hifz al-nasl). This study concludes that Iran’s framework cannot be transplanted into Indonesia without fundamentally restructuring civil, medical, and religious legal norms, underscoring the contextual limits of legal transplantation in comparative Islamic bioethics and Indonesian legal reform discourse.